Hardiness Of Paud Teachers (Study Of Paud Teachers In Himpaudi Kecamatan Candi): Hardiness Pada Guru Paud ( Studi Pada Guru Paud Di Himpaudi Kecamatan Candi) - Ifa Sintiyah; Ririn Dewanti D (Academia Open, 2021)
This research is presented by the problem of hardiness related to the unbalancing between the rights and obligations of early childhood teachers in HIMPAUDI Candi. This research uses a descriptive quantitative approach. The variable in this study is hardiness. The sampling technique used probability sampling with simple random sampling technique of 100 early childhood teachers in HIMPAUDI Candi. The data collection technique used the DRS (Dispositional Resilience Scale) II scale to measure hardiness and the Multiple Choice Single Response scale to measure the hardiness factors scale. Analysis of the data in this study used statistical tests with the help of the SPSS 20.0 and MS Excel 2019 programs. The reliability was 0.844 and the validity was> 0.30. The results of hardiness data on early childhood teachers in Candi with a moderate level of 89% and low level of 11%. The most influential factor is the dispositional factor (58%). The hardiness of early childhood teachers in Candi is also influenced by factors of age, years of service, education and salary.